(3GJaGbjI GdYhGFb GdafjI CeGe GdJLGQI (BTBT :s (3JbjjO Ce JMQjQ ddJLGQI GdOhdjI (B/s - (3fGTO, ShRj YOdjs ((3HjQhJ(B: s (3efThQGJ GdMdHj GdMbhbjI(B, s, 2010)
(3JGQjN GJaGbjI (BTBT (3h GdGNJdGaGJ GdGSGSjI Hjf (BTBT (3Whcjh h(BTBT (3defXeI GdJLGQI GdYGdejI (BWTO (3GdgOa GdQFjSj ef EJaGbjI (BTBTk (3, gjcd GJaGbjI GdYhGFb GdafjI CeGe GdJLGQI , GdBKGQ GdYGeI dGJaGbjI (BWTO (3Ydi GJaGbjI GdYhGFb GdafjI CeGe GdJLGQI , fWGb JWHjb EJaGbjI (BTBT (3, BKGQ EJaGbjI (BTBT (3Ydi JLGQI GdOhd GdfGejI (B.s
(3edGMb U(B.75s
Keywords: (3GdGJaGbjGJ GdJLGQjIs; (3GdJLGQIs; (3GdJLGQI GdNGQLjIs